Acute polyethylene microplastic (PE-MPs) exposure activates the intestinal mucosal immune network pathway in adult zebrafish (Danio rerio). (January 2023) - Yuan, Yin; Sepúlveda, Marisol S.; Bi, Baoliang; Huang, Yadong; Kong, Lingfu; Yan, Hui; Gao, Yu
Abstract: Polyethylene is one of the most important plastic types with the highest consumption in the world. Plastics are prone to photodegradation and turn into microplastics, which are magnified as they move across trophic levels. Microplastics would be able to penetrate into lymph even cross cell membranes, causing harm to the lymphatic and/or circulatory systems, accumulating in secondary organs, and impacting the immune system and cell health. The objective of this study was to test that the activation of the intestinal immune network might be caused by disruption of intestinal microbiota after exposure to different polyethylene microplastics (PE-MPs) concentrations (1, 10, 100, and 1000 μg/mL) in adult zebrafish ( Danio rerio ) for 7 days. The concentrations of PE-MPs (100 and 1000 μg/mL) exposure decreased the goblet cell coverage. The intestinal microbial diversity index (Shannon and Simpson) was increased at 100 and 1000 μg/mL PE-MPs concentrations. The relative abundance of intestinal dominant microbiota phylum Proteobacteria and Actinobacteria increased significantly ( P < 0.05); however, phylum Fusobacteria decreased significantly ( P < 0.05). The relative abundance of intestinal microbiota at level of genera showed varying degrees of elevation such as Acinetobacter (6.31-fold), Plesiomonas (4.80-fold), Flavobacterium (10.54-fold) and Pseudomonas (5.17-fold) in 1000 μg/mL PE-MPs. Intestinal innate immunity-complement C3 and C4 content first increased and then declined in a dose-dependent manner. Expression of genes from the intestinal immune network for mucosal immunoglobulin production were increased also in a dose-dependent manner. The expression of immune-related genes ( pigr, il10 and ighv4-5 ) were positively correlated with the relative abundance of genera Plesiomonas . In conclusion, PE-MPs increase the infection probability in the intestinal mucosa by altering the abundance of intestinal dominant microbiota at the level of phylum. PE-MPs exposure activated the intestinal immune network pathway for mucosal immunoglobulin production at a concentration of 100 or 1000 μg/mL for 7 days. Graphical abstract: Image 1 Highlights: PE-MPs decreased the goblet cell coverage in the intestine of zebrafish. Exposure to PE-MPs altered the abundance of intestinal dominant microbiota. Complement C3 and C4 first increased and then declined in a dose-dependent manner. Acute PE-MPs exposure activated the intestinal immune network pathway.